Desenvolvimento de um modelo de simulação para auxiliar o gerenciamento de sistemas de corte, carregamento e transporte de cana-de-açúcar - Silva, João Eduardo Azevedo Ramos da (2006)
Brazil is the greatest producer of sugar cane in the world. The 2004/2005 harvest season processed 360 million ton of sugar cane produced in 5.4 million hectares. The business related to this activity is responsible for 3 million direct and indirect jobs and much of Brazilian economy depends on this supply chain, from fertilizer and machine suppliers to final products delivery to their markets. The continuous feeding of sugar cane mills during the harvest season depends much on the management of harvesting, loading and transport operations of sugar cane from the farms to the mills. This delivery of sugar cane must be guaranteed to avoid the risk of stopping the industrial production of sugar and alcohol. This work focuses the development of a simulation model and its use as a management tool to evaluate the working shifts of agriculture machines operators of a sugar mill at São Paulo State. At first, this operations research technique is presented as a decision-making tool because it enables a previous evaluation before its implementation. In sequence, cutting, loading and transportation operations are described as well as the restrictions that bring difficulties to its management. Finally, the computer model developed is shown. It was used to evaluate and select the suitable working shift system regarding the requirements of cane delivery, the risk of lack of cane and the restriction of the daily working shift hours, established by labor legislation. Four scenarios were selected to evaluation. The first scenario considers all operators shift at 7:00 and 19:00 h (main schedule). The other scenarios consider a two, four and six hour delay of one of the cutting, loading and transportation teams in comparison to the main schedule. The model was efficient to represent the real system and much information was gathered to subsidize the decision. The scenario that considers a four hour delay of a team was select as the best as it reached most of the requirements of cane delivery, working hours limit and risk of lack of cane. The discussion is focused in the selected case, but similar works can be conducted to other sugar and alcohol mills or even to other processes of sugar and alcohol production system.